2012
DOI: 10.1248/bpb.b110670
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative Neolignans from <i>Saururus chinensis</i> against Human Cancer Cell Lines

Abstract: Activity-guided fractionation of an 80% EtOH extract from the aerial parts of Saururus chinensis led to isolation of three anti-proliferative neolignans (1-3) along with four flavonoids (4-7) and four aristolactams (8-11). Their chemical structures were identified by analysis of spectroscopic data. All compounds 1-11 were evaluated for their activities against 28 human cancer cell lines using an in vitro cell proliferation assay. Compounds 1-3 showed potent anti-proliferative activities against cervical (C33a,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Rhinacanthone role becomes quite significant since it is known to induce apoptotic cell death through multiple pathways as mentioned previously. Recent studies points to other molecules such as neolignans isolated from ethanolic extracts of the aerial parts of S. chinensis which has shown very strong anti-proliferative property as mentioned earlier (Lee et al, 2012). The IC 50 was found to be within 0.01-2.80 µM without any remarkable cytotoxic effects on human normal lung cells as a control.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Rhinacanthone role becomes quite significant since it is known to induce apoptotic cell death through multiple pathways as mentioned previously. Recent studies points to other molecules such as neolignans isolated from ethanolic extracts of the aerial parts of S. chinensis which has shown very strong anti-proliferative property as mentioned earlier (Lee et al, 2012). The IC 50 was found to be within 0.01-2.80 µM without any remarkable cytotoxic effects on human normal lung cells as a control.…”
Section: Discussionmentioning
confidence: 76%
“…Neolignans isolated from ethanolic extracts of the aerial parts of Saururus chinensis has shown antiproliferative property in another human cervical cancer cell line-C33a (Lee et al, 2012). The IC 50 was found to be within 0.01 µM-2.80 µM as indicated by cell proliferation assay without any remarkable cytotoxic effects on human normal lung cells as a control.…”
Section: Ethanolic Extractsmentioning
confidence: 94%
See 1 more Smart Citation
“…Some studies have reported the inhibition of melanoma formation and cell death in prostate and breast cancer cells using S. chinensis Baill constituents. The compound manassantin A isolated from SC-E has anti-proliferative effect in different cancer cell lines (Rao and Reddy, 1990;Feng et al, 2011;Lee et al, 2012). However, there were no studies on ER stressmediated apoptosis regarding SC-E Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Previous reports have shown that an extract of S. chinensis roots has various positive effects, including antioxidant, anti-inflammatory, antiviral, antihypertensive, anti-septic, and anti-cancer activities. [3][4][5][6][7] Sauchinone, a diastereomeric ligand and a potential anti-inflammatory compound, has been isolated from the n-hexane fraction of S. chinensis root extract. 8,9 However, the cellular and molecular mechanisms of the extract of the aerial parts of this plant and its active compounds have not been extensively characterized.…”
Section: Introductionmentioning
confidence: 99%